Brand perceptions of airports using social networks. (March 2019) - Gitto, Simone; Mancuso, Paolo
Abstract: The management of social media activities by airports is an emerging issue, and existing empirical literature on the measurement of brand perception in the airport industry is lacking. Usually, the measurement of brand perception is carried out by surveys, which are costly and rapidly become outdated. This study employs a newly developed algorithm to infer brand perceptions by mining the social connections of airports. Twitter accounts of 118 airports in the world are analysed by considering three emerging attributes in the airport industry: environment, disability and luxury. The paper shows how it is possible to identify the current positions of airports in the perception of the customers. Highlights: This study infers brand perceptions by mining the social connections of airports. Twitter accounts of 118 airports in the world are analysed. Three attributes are considered: environment, disability and luxury. It is identified the current positions of airports in the perception of the customers.